Effects of broken rice and taro root as sources of starch on the physical properties and microstructure of extruded fish feed - De Cruz, Clement Roy (2014)
Currently, Malaysia has great dependency on imported starch in production of floating fish pellets. The discovery of alternative sources of starch that are locally grown would promote a sustainable aquaculture feed industry in Malaysia. This study has examined the effects of native and modified starches (broken rice and taro) and varying extrusion processing variables on the physical properties of the pelleted fish feed. In the first part of the study, the factors studied were the effects of broken rice and taro inclusion (15%, 20%, and 25%), moisture level (30%, 35%, and 40%), and die head temperature (140, 150, 160 and 170°C) on the physical properties of the extruded pellets. The three barrel zones (70, 90,100°C) and screw speed (150 rpm) of the extruder were set constant throughout the extrusion process. All diets were processed using a single screw extruder. The findings showed that increasing broken rice and taro inclusion level, moisture level and die head temperature resulted in significant improvements on the physical properties of the extruded pellets. At 25% taro and broken rice starch level, 40% moisture level and 170°C die head temperature, the extruded pellets were able to float for more than 20 minutes. Likewise, as the die temperature was elevated the taro and broken rice starch have undergone a high degree of gelatinization evidenced by pellets with increased expansion ratio and better water stability as noted in water absorption and solubility indices values. In the second part of the study, two factorial experimental design were applied to investigate the effects of modified broken rice and taro inclusion level (15, 20, and 25 %) and extrusion die head temperature (125, 140, 155 and 170°C) on the physical properties of the extruded pellets. All the blends were preconditioned to 40% moisture content and then extruded using a single screw extruder. The three zones of the barrel temperature profile (70, 90 and 100°C) and screw speed (150 rpm) of the extruder were set constant throughout the extrusion cooking process. The findings elucidated that changes of modified broken rice and taro inclusion level and die head temperature had significant effects on water stability and floatability of the pellets. Changing level of modified broken rice and taro inclusion level from 15% to 25% increasd expansion ratio, floatability, and reduces bulk density values. Similarly, as the die temperature was elevated, the extruded pellets had higher expansion ratio, lower bulk density, higher floatability values and better water stability. The pellets extruded using modified broken rice and taro were very durable with fines produced at less than 1% for all treatments. Moreover, extruded pellets produced from 15% modified broken rice and taro inclusion level and 170°C die head temperature had high floatability values which were 100.00% and 93.33%, respectively. In conclusion, low inclusion of modified broken rice and taro starch could be used to manufacture high quality floating pellets with a very minimum optimization.